Komunikasi Persuasif Dalam Kepariwisataan - Neni Efrita (Universitas Islam Negeri Imam Bonjol Padang, 2014)
Nowadays, tourism has been growing all over the world including Indonesia and it has contributed to the country's foreign exchange. Rationally, the tourism developing sector showed a very rapid progress. This development was characterized by an increase in the number of tourists and tourist arrivals were expected to continue increasing frequency. Various efforts made by the government to develop the tourism sector by involving all relevant elements including through communication. Activities carried out by the government through the communication was an attempt to influence others, the process was called the persuasive communication. It was meant in order the tourist destinations of the various could be known through media of information that would be credible, as well will motivate travelers to determine how to assess multiple objects to consider and decide when to buy something or choose a tourist destination in Tourist Destination Areas (TDA). Persuasive communication in tourism activities will be effective if the practitioner was able to influence aspects of psychological, sociological and cultural aspects of society.